TO THE THEORY OF CURRENT AND VOLTAGE RESONANCE IN AN RLC OSCILLATOR CIRCUIT - Israilov M. (Web of Journals Publishing, 2025)
This article is devoted to current and voltage resonances in RLC oscillatory circuits. Particular attention is paid to the theoretical foundations of resonant processes.
Keywords: Resonance, oscillatory circuit, charge resonance, current resonance, voltage resonance, quality factor, differential equation, driving force, damped oscillation, damping coefficient, vector diagram.